Risk Identification of Private Entities in Public-Private Partnership (PPP) Projects for Water Supply Systems (SPAM) - Fakhrudin Naufal Ansori; Farida Rachmawati (SENTRI: Jurnal Riset Ilmiah, 2026)
The development of Water Supply System (SPAM) infrastructure through the Public-Private Partnership (PPP) scheme serves as a strategic solution to the state's fiscal limitations. However, its implementation faces challenges of high-risk complexity, particularly regarding the resilience of private partners post-construction. Failure to anticipate risks from the bidding stage often leads to financial distress or service failure during the concession period. This study aims to identify and map the dominant risk profile inherent to private entities during the partner selection phase of SPAM PPP projects. Using a descriptive quantitative method, data were collected through structured questionnaires from 7 expert respondents representing key stakeholders, selected via purposive and snowball sampling techniques. Data analysis was performed by calculating the Severity Index to map risks into a probability and impact matrix. The results reveal a significant risk distribution pattern, where the majority of risks are concentrated in the red zone (high/extreme risk) and orange zone, with none in the safe zone. Specifically, the study identified three highest-risk variables: "debt burden and financial instability" (financial aspect), "lack of capability in design and construction" (technical aspect), and "weakness in water system management capability" (managerial aspect). "Debt burden and financial instability" was identified as the most critical risk in the extreme quadrant, with the highest impact of 83%. Meanwhile, socio-political risks demonstrated significant impact despite having a lower probability. This study concludes that financial stability and technical competence are "killer factors" that must be prioritized in the evaluation criteria for private entity selection. The findings recommend that the Government Contracting Agency (PJPK) tighten the selection process regarding financial and technical aspects to ensure project sustainability.